(untitled) (Faridpur Medical College Journal, 2019)
Female genital fistula is a serious medical condition in which a perforation develops most commonly between bladder and vagina (VVF). Although the majority of genitourinary fistulas can be closed surgically, the successful closure depends on many factors. In this retrospective study, the records of 30 women with a mean age of 23.8 years were assessed; 13% of the VVF occurred after abdominal hysterectomy, 67% after Caesarean section, and 20% after difficult vaginal delivery. Six (20%) women had previous repair. The median duration of the VVF was 5.9 months. Of the 30 patients of VVF, 24 were high and 6 were low. Twenty seven had single fistula opening and 3 had two fistulous openings. An abdominal approach was used in 24 patients and vaginal approach in 6 patients. At a mean follow up of 24 months, the VVF was cured in 90% patients. In conclusion, surgical correction of the VVF is more successful when done earlier, probably in the first 6 months. Abdominal approach seems to be more successful technique and recurrent VVF being associated with lower success rates than primary repair. High variety also has good result. Faridpur Med. Coll. J. Jul 2018;13(2): 85-88